1980
DOI: 10.1530/acta.0.0930306
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid gland function during childhood and adolescence

Abstract: Serum thyrotrophin (TSH), thyroxine (T4), triiodothyronine (T3), thyroxine-binding globulin (TBG) and reverse T3 (rT3) were measured by radioimmunoassay in 175 girls and 187 boys aged 6.0 to 16.9 years, who were clinically healthy, and had negative serum antithyroglobulin and antimicrosomal antibodies. All the children had normal weight and height and were grouped at 12 months' intervals. In girls, TSH levels ranged between 5.3 \ m=+-\ 0.4 and 6.9 \ m=+-\ 0.5 \g=m\U/mlwithout significant changes with age; s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…This study expands our previous observations in relation to other hormonal (Parra et al 1980a) and non-hormonal parameters in the same population.…”
supporting
confidence: 88%
“…This study expands our previous observations in relation to other hormonal (Parra et al 1980a) and non-hormonal parameters in the same population.…”
supporting
confidence: 88%
“…Hypothyroidism in children is usually associated with retarded sexual maturation (22)(23)(24) although this relationship is complicated since, in some instances, hypothyroidism is associated with macro-orchidism, but without any outward signs of virilization (24). While there is general agreement that circulating levels of thyroid hormones decline throughout adolescence (25,26), the relationship between thyroid status and pubertal development is not clear. Corcoran and colleagues (27) reported that there was a peripubertal nadir in circulating levels of thyroid hormones in children, although it occurred 2 years later in boys than in girls.…”
Section: Introductionmentioning
confidence: 99%
“…The high incidence of abnormally elevated T3 serum concentrations in 27 children (22 boys and 5 girls) with positive thyroid antibodies and no symptoms of thyroid dysfunction, was the most striking finding, especially considering that the group with negative antibodies never showed such abnormality (Parra et al 1980). This would suggest that some patients with positive anti-thyroid anti¬ bodies already have thyroid dysfunction of variable degree, whose future evolution cannot be pre¬ dicted at this age.…”
Section: Discussionmentioning
confidence: 94%
“…The anti-thyroglobulin and antimicrosomal antibodies were detected by the tanned red cells haemagglutination technique (Fulthorpe & Raitt 1961). The validation analysis for each assay was carried out in our laboratories and has been previously published (Parra et al 1980). Of the original group of 520 children, 385 had negative thyroid antibodies and were used as a control group (Parra et al 1980).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation